Diagnosis of a huge right atrial thrombus during coronary artery bypass graft surgery - Senarslan, Omer (International Scientific Literature, Inc., 2013)
Patient: Male, 73 Final Diagnosis: Coronary artery thrombosis Symptoms: Angina pectoris • short of breath Medication: — Clinical Procedure: CABG Specialty: Cardiology OBJECTIVE: Management of emergency care BACKGROUND: Intra-operative formation of a thrombus in the right heart is rare and might be unrecognized. However, it can be associated with severe consequences, including pulmonary embolism and death. CASE REPORT: We report the case of a 73-year-old man who presented to the cardiologist with angina pectoris and rare shortness of breath. Coronary artery bypass grafting (CABG) was performed due to multi-vessel disease. Because of hemodynamic insufficiency, an intra-operative transesophageal echocardiogram (TEE) was performed and a huge free-floating thrombus was detected. Multiple thrombi were removed from the right heart and pulmonary arteries. The patient died after cardiopulmonary bypass support and 12 hours of intensive care. CONCLUSIONS: In this case report, we emphasize the importance of the TEE during the preoperational period and during CABG, as well as in the preoperative evaluation of pulmonary hypertension.